Meningkatkan Kemampuan Bergotong Royong Dengan Metode Problem Based Learning (PBL) Pada Kelas VII Dalam Pendidikan Agama Katolik Dan Budi Pekerti di SMP Negeri 3 Siberut Utara - Marinus Satoleuru (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Implementation of the independent curriculum is an effort to restore learning. The main characteristics of this curriculum that support learning recovery are the focus on essential material so that learning is deeper, prioritizing mutual cooperation for the development of competence and character through group learning around real contexts. Family is basically the first and main environment for every person in the process of growth and development. Students will grow into individuals who enjoy working together. Therefore, through the implementation of the Project for Strengthening the Profile of Pancasila Students (P-5) using the Problem Based Learning method, learning begins with problems experienced by students and can find solutions to these problems. Realizing that there is interdependence with each other. The family is a place for sowing the seeds of faith. In fact, in the family, faith is taught, lived, celebrated and practiced in daily life. In this way, you can feel and understand what you feel together as family members. In the end, students are able and willing to give and receive things that are considered valuable in the family so that students' interest and learning achievement in Catholic religious and character education at SMP Negeri 3 North Siberut increases significantly.